Identification of Bcl-6-dependent follicular helper NKT cells that provide cognate help for B cell responses. - Chang, P; Barral, P; Fitch, J; Pratama, A; Ma, C; Kallies, A; Hogan, J; Cerundolo, V; Tangye, S; Bittman, R; Nutt, S; Brink, R; et al. (2012)
Lipid antigens trigger help from natural killer T cells (NKT cells) for B cells, and direct conjugation of lipid agonists to antigen profoundly augments antibody responses. Here we show that in vivo, NKT cells engaged in stable and prolonged cognate interactions with B cells and induced the formation of early germinal centers. Mouse and human NKT cells formed CXCR5(+)PD-1(hi) follicular helper NKT cells (NKT(FH) cells), and this process required expression of the transcriptional repressor Bcl-6, signaling via the coreceptor CD28 and interaction with B cells. NKT(FH) cells provided direct cognate help to antigen-specific B cells that was dependent on interleukin 21 (IL-21). Unlike T cell-dependent germinal centers, those driven by NKT(FH) cells did not generate long-lived plasma cells. Our results demonstrate the existence of a Bcl-6-dependent subset of NKT cells specialized in providing help to B cells.